2015
DOI: 10.1002/aenm.201500658
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Electrocatalytic Activity of Boron‐Doped Graphene Derived from Boron Carbide

Abstract: A single material that can perform water oxidation and oxygen reduction reactions (ORR), also called bifunctional catalyst, represents a novel concept that emerged from recent materials research and that has led to applications in new‐generation energy‐storage systems, such as regenerative fuel cells. Here, metal/metal‐oxide free, doped graphene derived from rhombohedral boron carbide (B4C) is demonstrated to be an effective bifunctional catalyst for the first time. B4C, one of the hardest materials in nature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(53 citation statements)
references
References 38 publications
2
51
0
Order By: Relevance
“…[64][65][66][67][68][69][70] Rational design of carbon materials with multicomponent active centers can in principle lead to multifunctional catalysts for the ORR/OER. Typically, metal-free heteroatom (e.g., N)-doped carbon (C-N) and N-and transition metal-"co-doped" carbon (M-N-C, M = Fe or/and Co) are widely investigated.…”
Section: Carbon Materialsmentioning
confidence: 99%
“…[64][65][66][67][68][69][70] Rational design of carbon materials with multicomponent active centers can in principle lead to multifunctional catalysts for the ORR/OER. Typically, metal-free heteroatom (e.g., N)-doped carbon (C-N) and N-and transition metal-"co-doped" carbon (M-N-C, M = Fe or/and Co) are widely investigated.…”
Section: Carbon Materialsmentioning
confidence: 99%
“…[16] Secondly, vacancy defects (single/multi) and basal holes are intensively reported. [21] Generally, the extrinsic defects are introduced by heteroatom-doping way, including nonmetallic atoms like N, [22] P, [23] B, [25] S [26] and metallic atoms, [26] in which transition metal are increasingly popular due to a bunch of advantages such as low cost and high activity comparable to noble metals. [17] Finally, edges are considering as another type of defects in carbon nanomaterials.…”
Section: Types and Characterization Of Defective Carbon Materialsmentioning
confidence: 99%
“…Incorporation of foreign atoms in the sp 2 sites of graphene lattice can be an interesting prospect to tune the intrinsic properties of graphene [9,10]. Theoretical studies have revealed that substitutional doping of graphene with a heteroatom like nitrogen, boron, etc., can change the Fermi energy and introduce a band gap [11][12][13][14][15]. The doping with heteroatoms creates charged sites in the graphene lattice, as a result the spin and charge densities are redistributed bringing new functionalities [16].…”
Section: Introductionmentioning
confidence: 99%